Objectivity in valuation techniques - Sipan, Ibrahim; Ab. Rahman, Rosdi (Fakulti Kejuruteraan dan Sains Geoinformasi, 1996)
The issue of valuation accuracy is important for real estate professionals. The issue of accuracy and the techniques of valuation for assessing it has been the subject of recent academic research and debate. This paper focuses on two main areas related to the topic of objectivity in valuation techniques. Firstly, it examined part of the methodological problem in traditional method of valuation including subjective elements and suggestions to improve it by using quantitative techniques to valuation. Finally, the element of risk and uncertainties in traditional approach should he treated by incorporating risk analysis tool to the valuation techniques. It is concluded that the application of quantitative techniques and risk analysis tools in valuation techniques will lead to produce more objective valuation.